Attracting and retaining qualified nurses in aged and dementia care: outcomes from an Australian study. (7th March 2013) - Chenoweth, Lynn; Merlyn, Teri; Jeon, Yun‐Hee; Tait, Fiona; Duffield, Christine
<x xml:space="preserve">Abstract</x> Aim To identify key issues and factors affecting retention of qualified nurses who care for older people and persons with dementia in Australian acute, subacute, community and residential health‐care settings. Background As the number of older people with chronic conditions needing health care continues to increase research is needed to optimize nurse retention. Methods Qualified nurses were surveyed with a set of items derived from four published nurse workforce questionnaires (Cronbach's alpha range 0.75–0.96). There were 3983 complete responses and 10 focus groups with 58 volunteer survey respondents. Results In addition to reporting a number of workplace issues, nurses also reported reasonable levels of satisfaction. Intrinsic factors related to caregiving, work relations and colleague support. Extrinsic factors included professional opportunities and organisational support. Conclusions Altruism is a primary motivation for choosing to nurse older people and persons with dementia. Nurses are most positive when they feel valued and supported by their organisation and colleagues, through education, training, supervision, mentoring opportunities and appropriate remuneration. Implications for nursing management Nursing managers need to take positive steps to address the organisational factors outlined in this paper that either inhibit or promote nurse retention.